1993
DOI: 10.3928/0098-9134-19930901-07
|View full text |Cite
|
Sign up to set email alerts
|

GERIATRIC FALLS: Prevention Strategies for the Staff

Abstract: 1. Multiple falls and injuries are more prevalent among elderly over the age of 75 and are the second leading cause of accidental death in the elderly. The risk for falling is noted to be significantly greater in the hospitalized elderly. 2. Review of retrospective quality improvement chart audits revealed that peak fall times were associated with the patient's need for toileting, rest, and obtaining nutrition and hydration. 3. The MetroHealth Falls Prevention Program is based on simple proactive measures to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The care plans and precise interventions are not always adequately described in the papers. In one case, 74 a significant association was found between incidence of falls and time of day, leading to a concentration of effort at times of highest risk.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The care plans and precise interventions are not always adequately described in the papers. In one case, 74 a significant association was found between incidence of falls and time of day, leading to a concentration of effort at times of highest risk.…”
Section: Resultsmentioning
confidence: 89%
“…The prospective study with parallel control and the prospective studies with historical controls provided enough information to allow the calculation of rate ratios and confidence intervals. There were a further 10 prospective studies with historical controls where only fall rates were described, 74–84 but these could not be subjected to meta‐analysis. There was a tendency for the most rigorously controlled trials to produce the smallest effects, with the most powerful effects being for uncontrolled trials where only fall rates were described (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…1, 2 Appropriate footwear can help people maintain mobility, independence, freedom from pain, and general well-being, [1][2][3][4][5][6] whereas inappropriate shoes may deprive elderly people of mobility and contribute to foot problems 7-10 and falls. [12][13][14][15][16][17][18][19] In a study of 107 people (88 women; mean age, 77 years) who had been admitted to a hospital after fracturing the neck of the femur, it was found that slippers were worn at the time of the fall in over 30% of cases. [12][13][14][15][16][17][18][19] In a study of 107 people (88 women; mean age, 77 years) who had been admitted to a hospital after fracturing the neck of the femur, it was found that slippers were worn at the time of the fall in over 30% of cases.…”
mentioning
confidence: 99%
“…Credit was divided among the researchers. The nursing professor took the lead in writing the results of the project (Turkoski et al, 1997) and a nurse manager (see Table 1) took first-author responsibility for writing the manuscript that precipitated this research (Brady et al, 1993). All members of the team are listed in the authorship of both manuscripts, because all participated in writing sections of the papers.…”
Section: Exemplarmentioning
confidence: 99%